Solving a damped spring-mass system via the MA-simulation function - Jain, Shobha; Radenović, Stojan N.; Jain, Shishir (Vojnotehnički glasnik / Military Technical Courier, 2025)
Introduction/purpose: In an interesting article, Perveen & Imdad (2019) introduced the notion of an MA-simulation function, and utilized it to prove the existence of a fixed point for a self mapping through α-admisibilty and the continuity of the self-map in a fuzzy metric space. The purpose of this paper is to establish a unique fixed point theorem for an MA-contractive mapping by relaxing the condition of continuity and α-admissibilty of the map in a fuzzy metric space. As an application of our result, we study the existence and uniqueness of the solution to the damped spring-mass system. The article includes an example which shows the validity of our results.Methods: The fixed point method with an MA-simulation function was used.Results: A unique fixed point for a self map in a fuzzy metric space is obtained.Conclusions: A fixed point of the self maps is obtained without the continuity and α-admissibility of the self map via the MA-simulation function. Also, the existence and uniqueness of the solution of a damped spring-mass system in the setting of a fuzzy metric space is obtained.
Keywords: fuzzy metric space; M-Cauchy sequence; fixed points; MA-simulation function